Carbon black slurry for negative electrode formation, method for producing coating liquid for negative electrode formation, method for producing negative electrode, and method for producing battery
Patent Information
- Application Number
- CN202580023920.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-02-25
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies struggle to effectively utilize small-particle-size carbon black to manufacture a negative electrode with low electrode resistance, thus limiting the performance improvement of lithium-ion secondary batteries.
A slurry composed of carbon black with an average primary particle size of less than 22 nm, aqueous solvent, and dispersant is formed through a specific mixing and dispersion process to create a coating liquid for forming a negative electrode with excellent conductivity. This coating liquid is then applied to the current collector to form a composite material layer.
This technology enables the manufacture of a negative electrode with low electrode resistance using carbon black with smaller primary particle size, thereby improving the performance of lithium-ion secondary batteries, especially showing better application potential in electric vehicles and natural energy generation/storage systems.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This disclosure relates to a method for manufacturing a carbon black slurry for forming a negative electrode, a coating liquid for forming a negative electrode, a method for manufacturing a negative electrode, and a method for manufacturing a battery. Background Technology
[0002] Lithium-ion rechargeable batteries are widely used as power sources for small electronic devices such as smartphones and tablet computers. A typical lithium-ion rechargeable battery comprises electrodes, a separator, and an electrolyte. The electrodes are manufactured by coating a composite material slurry (obtained by dispersing active materials, conductive agents, and binders in a dispersion medium) onto a current collector and then drying it, thereby forming a composite material layer.
[0003] For example, Patent Document 1 discloses a negative electrode for a non-aqueous electrolyte secondary battery, which uses a negative electrode active material, a conductive material, and a binder of polyvinyl alcohol resin with a saponification degree of 87 to 99.9 mol% as the electrode binder layer.
[0004] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2016-181414 Summary of the Invention
[0005] The problem the invention aims to solve In recent years, with the development of electric vehicles and natural energy power generation / storage systems, there has been a demand for further improvements in the characteristics of secondary batteries.
[0006] The purpose of this disclosure is to provide a carbon black slurry for forming a negative electrode, which enables the use of carbon black with a small primary particle size to achieve a negative electrode with low electrode resistance. Furthermore, the purpose of this disclosure is to provide a method for manufacturing a coating liquid for forming a negative electrode, which uses carbon black with a small primary particle size to manufacture a coating liquid for forming a negative electrode with low electrode resistance. Additionally, the purpose of this disclosure is to provide a method for manufacturing a negative electrode, which uses carbon black with a small primary particle size to manufacture a negative electrode with low electrode resistance. Finally, the purpose of this disclosure is to provide a method for manufacturing a battery, which uses carbon black with a small primary particle size to manufacture a battery having a negative electrode with low electrode resistance.
[0007] Technical means to solve the problem This disclosure relates, for example, to the following [1] to [9].
[0008] [1] A carbon black slurry for negative electrode formation, comprising carbon black with an average primary particle size of less than 22 nm and an aqueous solvent, wherein the carbon black content is more than 50% by mass based on the total solid content, and the median particle size (D50) of the carbon black is more than 0.1 μm and less than 1 μm in the volume-based particle size distribution determined by laser diffraction and scattering method.
[0009] [2] The carbon black slurry for forming the negative electrode according to [1] further contains a dispersant.
[0010] [3] According to the carbon black slurry for forming the negative electrode as described in [2], the content of the dispersant is 10 parts by mass or more and 25 parts by mass or less relative to 100 parts by mass of the carbon black.
[0011] [4] The carbon black slurry for negative electrode formation according to [2] or [3], wherein the dispersant is selected from the group consisting of polyvinylpyrrolidone and sodium carboxymethyl cellulose.
[0012] [5] The carbon black slurry for forming a negative electrode according to any one of [1] to [4], wherein the specific surface area of the carbon black is 150 m². 2 / g or more and 400m 2 / g or less.
[0013] [6] The carbon black slurry for forming a negative electrode according to any one of [1] to [5], wherein the aqueous solvent is water and the content of the organic solvent is less than 1% by mass.
[0014] [7] A method for manufacturing a coating liquid for forming a negative electrode, comprising a step of mixing a carbon black slurry for forming a negative electrode, a negative electrode active material and a binder as described in any one of [1] to [6].
[0015] [8] A method for manufacturing a negative electrode includes a step of coating a negative electrode forming coating liquid manufactured by the manufacturing method described in [7] onto a current collector to obtain a negative electrode having the current collector and a composite material layer disposed on the current collector.
[0016] [9] A method for manufacturing a battery includes a step of coating a negative electrode forming coating liquid manufactured by the manufacturing method described in [7] onto a current collector to obtain a negative electrode having the current collector and a composite material layer disposed on the current collector.
[0017] The effects of the invention According to this disclosure, a carbon black slurry for forming a negative electrode is provided, which can achieve a negative electrode with low electrode resistance using carbon black with a small primary particle size. Furthermore, according to this disclosure, a method for manufacturing a coating liquid for forming a negative electrode is provided, which can use carbon black with a small primary particle size to manufacture a coating liquid for forming a negative electrode capable of forming a negative electrode with low electrode resistance. Furthermore, according to this disclosure, a method for manufacturing a negative electrode is provided, which uses carbon black with a small primary particle size to manufacture a negative electrode with low electrode resistance. Moreover, according to this disclosure, a method for manufacturing a battery is provided, which uses carbon black with a small primary particle size to manufacture a battery having a negative electrode with low electrode resistance. Detailed Implementation
[0018] The preferred embodiments of this disclosure will now be described in detail.
[0019] (Carbon black slurry for negative electrode formation) The carbon black slurry for forming the negative electrode in this embodiment (hereinafter also referred to as "the slurry of this embodiment" or "slurry") contains carbon black with an average primary particle size of 22 nm or less and an aqueous solvent.
[0020] In the slurry of this embodiment, the carbon black content is 50% by mass or more, based on the total solids content. Furthermore, in the slurry of this embodiment, the median particle size (D50) of the carbon black in the volumetric particle size distribution determined by laser diffraction and scattering method is 0.1 μm or more and 1 μm or less.
[0021] The slurry of this embodiment can be described as a slurry with a specified carbon black as the main component, and the carbon black is dispersed in a manner that satisfies a specified median particle size (D50).
[0022] Traditionally, in the formation of the negative electrode, a conductive material (carbon black), the negative electrode active material, and a binder are dispersed in a dispersion medium to form a coating solution, which is then coated onto a current collector to form a composite material layer. However, according to the inventors' findings, when carbon black with a small average primary particle size (e.g., carbon black with an average primary particle size of less than 22 nm) is used as the conductive material, the carbon black agglomerates when dispersed in the dispersion medium, sometimes failing to achieve the desired conductivity. The inventors have discovered that by pre-preparing a slurry in which carbon black is dispersed in an aqueous solvent and using this slurry for negative electrode formation, excellent conductivity can be obtained even when using carbon black with a small average primary particle size, and a negative electrode with low electrode resistance can be formed.
[0023] According to the slurry of this embodiment, a negative electrode with low electrode resistance can be obtained by using carbon black with a small average primary particle size.
[0024] The slurry of this embodiment contains carbon black and an aqueous solvent, and may further contain a dispersant. The components are described in detail below.
[0025] (Carbon black) Carbon black can be acetylene black, furnace black, channel black, etc., with acetylene black being the preferred option.
[0026] The average primary particle size of the carbon black is less than 22 nm. From the viewpoint of more significantly obtaining the effects brought about by the slurry preparation mentioned above, it can also be less than 21 nm or less than 20 nm. The average primary particle size of the carbon black can be, for example, greater than 5 nm, or greater than 10 nm, greater than 15 nm, or greater than 17 nm. That is, the average primary particle size of the carbon black can be, for example, 5–22 nm, 5–21 nm, 5–20 nm, 10–22 nm, 10–21 nm, 10–20 nm, 15–22 nm, 15–21 nm, 15–20 nm, 17–22 nm, 17–21 nm, or 17–20 nm.
[0027] In addition, in this specification, the average primary particle size of carbon black refers to the value determined by the following method.
[0028] <Method for determining the average primary particle size> Five images at 100,000x magnification were captured using a JEM-2000FX transmission electron microscope (manufactured by Nippon Electron Corporation). The particle size of more than 200 randomly selected primary particles was determined by image analysis, and the average number of these particles was calculated for measurement. The particle size represents the equivalent circle diameter of the primary particle.
[0029] The specific surface area of carbon black can be, for example, 150 m². 2 / g or more, or 200m 2 / g or more, 250m 2 / g or more or 270m 2 / g or more. When the specific surface area of carbon black is large, the number of contact points with the negative electrode active material and the current collector increases, making it easier to obtain good conductivity and liquid retention. In addition, carbon black with a large specific surface area is more likely to agglomerate when mixed with the dispersion medium, so the above-mentioned slurry-like effect is more significant. Furthermore, the specific surface area of carbon black can be, for example, 400 m². 2 Below / g, it can also be 370m 2 / g or less, 350m 2 / g or less, 320m 2 / g or less or 310m 2 / g or less. That is, the specific surface area of carbon black can be, for example, 150-400 m². 2 / g, 150~370m 2 / g, 150~350m 2 / g, 150~320m 2 / g, 150~310m 2 / g, 200~400m 2 / g, 200~370m 2 / g, 200~350m 2 / g, 200~320m 2 / g, 200~310m 2 / g, 250~400m 2 / g, 250~370m 2 / g, 250~350m 2 / g, 250~320m 2 / g, 250~310m 2 / g, 270~400m 2 / g, 270~370m 2 / g, 270~350m 2 / g, 270~320m 2 / g or 270~310m 2 / g.
[0030] In addition, in this specification, the specific surface area of carbon black refers to the nitrogen adsorption specific surface area measured by the single-point method according to JIS K6217-2:2017.
[0031] The DBP oil absorption capacity of carbon black can be, for example, 300 mL / 100 g or more, or 310 mL / 100 g or more, or 320 mL / 100 g or more, or 330 mL / 100 g or more. Furthermore, the DBP oil absorption capacity of carbon black can be, for example, 500 mL / 100 g or less, or 450 mL / 100 g or less, 400 mL / 100 g or less, or 380 mL / 100 g or less. When the DBP oil absorption capacity of carbon black is within the above ranges, interparticle interactions are suppressed, resulting in good dispersibility. That is, the DBP oil absorption of carbon black can be, for example, 300-500 mL / 100g, 300-450 mL / 100g, 300-400 mL / 100g, 300-380 mL / 100g, 310-500 mL / 100g, 310-450 mL / 100g, 310-400 mL / 100g, 310-380 mL / 100g, 320-500 mL / 100g, 320-450 mL / 100g, 320-400 mL / 100g, 320-380 mL / 100g, 330-500 mL / 100g, 330-450 mL / 100g, 330-400 mL / 100g, or 330-380 mL / 100g.
[0032] In addition, in this specification, the DBP oil absorption of carbon black is an indicator of the ability of the carbon black particles to absorb dibutyl phthalate (DBP) through the pores formed on the surface and structure of the carbon black particles, and refers to the value measured by the following method.
[0033] <Determination of DBP oil absorption> The DBP oil absorption in this specification refers to the DBP absorption value measured according to the method described in JIS K6221, which is converted into the measured value according to the method described in JIS K6217-4:2008 by the following formula (a).
[0034] DBP absorption = (A - 10.974) / 0.7833...(a) [In the formula, A represents the DBP absorbance value determined according to the method described in JIS K6221.] Based on the total solid content, the carbon black content in the slurry of this embodiment is 50% by mass or more, or it may be 60% by mass or more, 70% by mass or more, or 80% by mass or more.
[0035] (Aqueous solvent) Aqueous solvents are used as dispersion media for dispersing carbon black.
[0036] Aqueous solvents can be water or a mixture of water and an organic solvent. Any organic solvent that is miscible with water is acceptable. Examples of water-miscible organic solvents include alcohols such as ethanol, acetone, acetonitrile, and toluene.
[0037] From the perspective of reducing environmental impact and manufacturing costs, water is the preferred aqueous solvent.
[0038] From the viewpoint of environmental impact and manufacturing cost, the slurry of this embodiment preferably has a low content of organic solvents. In the slurry of this embodiment, the content of organic solvents may be less than 1% by mass, less than 0.5% by mass, less than 0.1% by mass, less than 0.05% by mass, or even 0% by mass.
[0039] In the slurry of this embodiment, the content of aqueous solvent is not particularly limited, and can be adjusted as needed to meet the concentration of solid components.
[0040] The solid content concentration of the slurry in this embodiment can be, for example, 5% by mass or more, or 7% by mass or more, 9% by mass or more, or 10% by mass or more. Alternatively, the solid content concentration in this embodiment can be, for example, 50% by mass or less, or 40% by mass or less, 30% by mass or less, or 20% by mass or less. By setting such a solid content concentration, mixing with the negative electrode active material and binder becomes easier when manufacturing the coating liquid for forming the negative electrode. That is, the solid content concentration of the slurry in this embodiment can be, for example, 5–50% by mass, 5–40% by mass, 5–30% by mass, 5–20% by mass, 7–50% by mass, 7–40% by mass, 7–30% by mass, 7–20% by mass, 9–50% by mass, 9–40% by mass, 9–30% by mass, 9–20% by mass, 10–50% by mass, 10–40% by mass, 10–30% by mass, or 10–20% by mass.
[0041] (Dispersant) The slurry in this embodiment may further contain a dispersant. The dispersant only needs to have the function of assisting the dispersion of carbon black in an aqueous solvent.
[0042] The dispersant can be, for example, a water-soluble polymer.
[0043] In addition, in this specification, "solids composition" refers to the components remaining after the aqueous solvent, organic solvent, etc., in the slurry or coating solution for forming the negative electrode has been vaporized. For example, water-soluble polymers dissolved in aqueous solvents are also included in the solids composition.
[0044] Examples of dispersants include: polyvinylpyrrolidone, sodium carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, polyethylene, polypropylene, polymethyl methacrylate, polyvinyl chloride, polyvinylidene chloride, polyvinyl acetate, polyacrylic acid, sodium polyacrylate, polyvinyl butyral, polyacrylamide, polyurethane, polydimethylsiloxane, epoxy resin, acrylic resin, polyester resin, melamine resin, phenolic resin, various rubbers, lignin, pectin, gelatin, xanthan gum, vegan gum, succinyl polysaccharide, polyvinyl acetal, cellulose resins, polyepoxides, polyvinyl ethers, polyvinyl alcohol, cellulose nanofibers, sodium alginate, etc.
[0045] From the viewpoint of easily obtaining the desired particle size distribution, the dispersant is preferably selected from the group consisting of polyvinylpyrrolidone and sodium carboxymethyl cellulose.
[0046] When the dispersant is polyvinylpyrrolidone (PVP), the weight-average molecular weight (Mw) of PPVP can be, for example, above 10,000, or above 20,000, 30,000, or 40,000. A higher weight-average molecular weight of PPVP improves the dispersion stability of carbon black and the adhesion between carbon black and the negative electrode active material. Conversely, the weight-average molecular weight (Mw) of PPVP can be below 500,000, or below 400,000, 350,000, or 300,000. A lower weight-average molecular weight of PPVP improves the dispersibility of carbon black, making it easier to achieve the aforementioned particle size distribution. That is, the weight-average molecular weight (Mw) of polyvinylpyrrolidone can be, for example, 10,000–500,000, 10,000–400,000, 10,000–350,000, 10,000–300,000, 20,000–500,000, 20,000–400,000, 20,000–350,000, 20,000–300,000, 30,000–500,000, 30,000–400,000, 30,000–350,000, 30,000–300,000, 40,000–500,000, 40,000–400,000, 40,000–350,000, or 40,000–300,000.
[0047] In the slurry of this embodiment, the content of the dispersant relative to 100 parts by mass of carbon black can be, for example, 5 parts by mass or more, 8 parts by mass or more, or 10 parts by mass or more. A higher content of dispersant improves the dispersibility of the carbon black, making it easier to obtain the aforementioned particle size distribution. Conversely, the content of the dispersant relative to 100 parts by mass of carbon black can be, for example, 40 parts by mass or less, 30 parts by mass or less, or 25 parts by mass or less. A lower content of dispersant tends to result in a lower internal resistance in the composite material layer. That is, the content of the dispersant relative to 100 parts by mass of carbon black can be, for example, 5–40 parts by mass, 5–30 parts by mass, 5–25 parts by mass, 8–40 parts by mass, 8–30 parts by mass, 8–25 parts by mass, 10–40 parts by mass, 10–30 parts by mass, or 10–25 parts by mass.
[0048] In the slurry of this embodiment, the median particle size (D50) of the carbon black, as measured by laser diffraction and scattering, is 0.1 μm or more and 1 μm or less. The median particle size (D50) may also be 0.15 μm or more, or 0.2 μm or more. Furthermore, the median particle size (D50) may be 0.8 μm or less, 0.6 μm or less, 0.4 μm or less, or 0.3 μm or less. That is, the median particle size (D50) can be, for example, 0.1–1 μm, 0.1–0.8 μm, 0.1–0.6 μm, 0.1–0.4 μm, 0.1–0.3 μm, 0.15–1 μm, 0.15–0.8 μm, 0.15–0.6 μm, 0.15–0.4 μm, 0.15–0.3 μm, 0.2–1 μm, 0.2–0.8 μm, 0.2–0.6 μm, 0.2–0.4 μm, or 0.2–0.3 μm.
[0049] In the above particle size distribution, D90 can be, for example, less than 5 μm, less than 3 μm, less than 2 μm, or less than 1 μm. D90 can be, for example, greater than 0.15 μm, or greater than 0.2 μm, greater than 0.3 μm, greater than 0.4 μm, or greater than 0.5 μm. That is, D90 can be, for example, 0.15–5 μm, 0.15–3 μm, 0.15–2 μm, 0.15–1 μm, 0.2–5 μm, 0.2–3 μm, 0.2–2 μm, 0.2–1 μm, 0.3–5 μm, 0.3–3 μm, 0.3–2 μm, 0.3–1 μm, 0.4–5 μm, 0.4–3 μm, 0.4–2 μm, 0.4–1 μm, 0.5–5 μm, 0.5–3 μm, 0.5–2 μm, or 0.5–1 μm.
[0050] In the above particle size distribution, the proportion of particles with a diameter of 5 μm or larger can be less than 2% by volume, or less than 1% by volume, less than 0.5% by volume, or less than 0.4% by volume, or even 0% by volume. A lower proportion of particles with a diameter of 5 μm or larger means less secondary aggregates of carbon black, which can lead to a more uniform conductive path within the electrode structure.
[0051] The slurry of this embodiment can be manufactured, for example, by the following method.
[0052] (Method for preparing slurry) The slurry of this embodiment can be manufactured, for example, by a manufacturing method that includes a step of mixing carbon black and an aqueous solvent.
[0053] In the above process, carbon black and aqueous solvents can be mixed to meet the aforementioned particle size distribution characteristics. In other words, the mixing method and conditions in the above process can be appropriately selected to ensure that the particle size distribution in the slurry meets the aforementioned characteristics.
[0054] In the above process, a dispersant can be further mixed.
[0055] The method for manufacturing the slurry may include, for example, a first mixing step of mixing carbon black with a portion of an aqueous solvent to obtain a first mixture; a second mixing step of mixing the first mixture with the remaining portion of the aqueous solvent to obtain a second mixture; and a dispersion step of dispersing the second mixture to obtain the slurry. According to this manufacturing method, the carbon black can be dispersed by breaking down secondary aggregates (agglomerates) while maintaining the primary aggregate (agglomerate) structure. By maintaining the structure of the primary aggregates (agglomerates), conductive paths are easily formed in the composite material layer, making it easier to obtain a negative electrode with lower electrode resistance.
[0056] The first mixture contains carbon black and a portion of an aqueous solvent, and the second mixture contains carbon black and an aqueous solvent.
[0057] In the first mixing step, a portion of the dispersant may be further mixed. That is, the first mixture may contain carbon black, a portion of an aqueous solvent, and a portion of the dispersant. Furthermore, in the second mixing step, the remaining portion of the dispersant may be further mixed. That is, the second mixture may contain carbon black, an aqueous solvent, and the dispersant.
[0058] The amount of aqueous solvent mixed in the first mixing step, relative to the total amount of aqueous solvent, can be, for example, 30% by mass or more, or 40% by mass or more, 50% by mass or more, or 55% by mass or more. Furthermore, the amount of aqueous solvent mixed in the first mixing step, relative to the total amount of aqueous solvent, can be, for example, 80% by mass or less, or 75% by mass or less, 70% by mass or less, or 65% by mass or less. That is, the amount of aqueous solvent mixed in the first mixing step, relative to the total amount of aqueous solvent, can be, for example, 30–80% by mass, 30–75% by mass, 30–70% by mass, 30–65% by mass, 40–80% by mass, 40–75% by mass, 40–70% by mass, 40–65% by mass, 50–80% by mass, 50–75% by mass, 50–70% by mass, 50–65% by mass, 55–80% by mass, 55–75% by mass, 55–70% by mass, or 55–65% by mass.
[0059] The amount of dispersant mixed in the first mixing step, relative to the total amount of dispersant, can be, for example, 30% by mass or more, or 40% by mass or more, 50% by mass or more, or 55% by mass or more. Alternatively, the amount of dispersant mixed in the first mixing step, relative to the total amount of dispersant, can be, for example, 80% by mass or less, or 75% by mass or less, 70% by mass or less, or 65% by mass or less. That is, the amount of dispersant mixed in the first mixing step, relative to the total amount of dispersant, can be, for example, 30–80% by mass, 30–75% by mass, 30–70% by mass, 30–65% by mass, 40–80% by mass, 40–75% by mass, 40–70% by mass, 40–65% by mass, 50–80% by mass, 50–75% by mass, 50–70% by mass, 50–65% by mass, 55–80% by mass, 55–75% by mass, 55–70% by mass, or 55–65% by mass.
[0060] There are no particular limitations on the mixing method in the first mixing process; any known mixing method can be appropriately selected.
[0061] From the viewpoint of easily dispersing carbon black while maintaining its primary aggregates (aggregates), the mixing method in the first mixing process can be, for example, mixing using a rotary mixer.
[0062] The amount of aqueous solvent mixed in the second mixing step can be the total amount of the remaining aqueous solvent not used in the first mixing step. The amount of aqueous solvent mixed in the second mixing step can be, for example, 20% by mass or more, or 25% by mass or more, 30% by mass or more, or 35% by mass or more. Furthermore, the amount of aqueous solvent mixed in the second mixing step can be, for example, 70% by mass or less, or 60% by mass or less, 50% by mass or less, or 45% by mass or less. That is, the amount of aqueous solvent mixed in the second mixing step can be, for example, 20–70% by mass, 20–60% by mass, 20–50% by mass, 20–45% by mass, 25–70% by mass, 25–60% by mass, 25–50% by mass, 25–45% by mass, 30–70% by mass, 30–60% by mass, 30–50% by mass, 30–45% by mass, 35–70% by mass, 35–60% by mass, 35–50% by mass, or 35–45% by mass.
[0063] The amount of dispersant mixed in the second mixing step can be the total amount of remaining dispersant not used in the first mixing step. The amount of dispersant mixed in the second mixing step can be, for example, 20% by mass or more, or 25% by mass or more, 30% by mass or more, or 35% by mass or more. Alternatively, the amount of dispersant mixed in the second mixing step can be, for example, 70% by mass or less, or 60% by mass or less, 50% by mass or less, or 45% by mass or less. That is, the amount of dispersant mixed in the second mixing step can be, for example, 20–70% by mass, 20–60% by mass, 20–50% by mass, 20–45% by mass, 25–70% by mass, 25–60% by mass, 25–50% by mass, 25–45% by mass, 30–70% by mass, 30–60% by mass, 30–50% by mass, 30–45% by mass, 35–70% by mass, 35–60% by mass, 35–50% by mass, or 35–45% by mass.
[0064] There are no particular limitations on the mixing method in the second mixing process; any known mixing method can be appropriately selected.
[0065] From the viewpoint that it is easy to disperse carbon black while maintaining the primary aggregates (aggregates), the mixing method in the second mixing process can be, for example, mixing using a rotary mixer.
[0066] In the dispersion process, the second mixture is dispersed to obtain a slurry. The dispersion process is not particularly limited and can be appropriately selected from known dispersion methods. Examples of dispersion methods include media dispersion using a bead mill, media-free dispersion using a disperser, homogenizer, planetary mixer, or high-pressure homogenizer.
[0067] In the dispersion process, dispersion treatment can be performed to meet the aforementioned particle size distribution characteristics. In other words, the dispersion treatment method and conditions can be appropriately selected to ensure that the particle size distribution in the slurry meets the aforementioned characteristics.
[0068] The slurry of this embodiment is suitable as a raw material for manufacturing a coating solution for negative electrode formation. A coating solution for negative electrode formation can be easily manufactured by mixing the slurry of this embodiment, the negative electrode active material, and the binder.
[0069] (Coating solution for negative electrode formation) The coating solution for forming the negative electrode in this embodiment is a mixture of the above-mentioned slurry, negative electrode active material, and binder, and contains carbon black, an aqueous solvent, negative electrode active material, and binder. The coating solution for forming the negative electrode in this embodiment may further contain a dispersant.
[0070] The carbon black in the coating solution for forming the negative electrode is derived from the carbon black in the slurry described above. Therefore, the same carbon black as described above can be used as the carbon black in the coating solution for forming the negative electrode.
[0071] The aqueous solvent in the coating solution for forming the negative electrode includes an aqueous solvent derived from the aforementioned slurry. In addition to the aqueous solvent derived from the aforementioned slurry, the coating solution for forming the negative electrode may further contain an aqueous solvent. That is, the coating solution for forming the negative electrode may be a product further mixed with an aqueous solvent that is a component other than the aforementioned slurry.
[0072] As an aqueous solvent in the coating solution for forming the negative electrode, the same aqueous solvents as those described above can be used. As an aqueous solvent mixed as a component other than the above-described slurry, it can be the same as the aqueous solvent in the above-described slurry.
[0073] The dispersant in the coating solution for forming the negative electrode includes a dispersant derived from the aforementioned slurry. In addition to the dispersant derived from the aforementioned slurry, the coating solution for forming the negative electrode may further contain a dispersant. That is, the coating solution for forming the negative electrode may be a product further mixed with a dispersant that is a component other than the aforementioned slurry.
[0074] As the negative electrode active material, known negative electrode active materials for secondary batteries can be used without particular restrictions.
[0075] Examples of anode active materials include: carbon materials (such as graphite, non-graphitized carbon, easily graphitized carbon, polyphenylene, etc.), silicon materials (such as silicon monoxide, etc.), lithium metal, lithium titanate, or mixtures thereof.
[0076] The negative electrode active material may contain, for example, carbon and silicon. In this case, the silicon content relative to 100 parts by mass of carbon can be, for example, 5 parts by mass or more, or 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more. A higher silicon content is expected to increase energy density. Conversely, the silicon content relative to 100 parts by mass of carbon can be, for example, 90 parts by mass or less, or 70 parts by mass or less, 50 parts by mass or less, or 30 parts by mass or less. A lower silicon content improves conductivity and makes it easier to obtain lower electrode resistance. That is, relative to 100 parts by mass of carbon material, the content of silicon material can be, for example, 5-90 parts by mass, 5-70 parts by mass, 5-50 parts by mass, 5-30 parts by mass, 10-90 parts by mass, 10-70 parts by mass, 10-50 parts by mass, 10-30 parts by mass, 15-90 parts by mass, 15-70 parts by mass, 15-50 parts by mass, 15-30 parts by mass, 20-90 parts by mass, 20-70 parts by mass, 20-50 parts by mass, or 20-30 parts by mass.
[0077] As a binder, known binders for composite layers in the negative electrode can be used without particular restriction.
[0078] Examples of adhesives include: polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene copolymer, polyvinyl alcohol, sodium polyacrylate, polyacrylic acid, polyacrylate, polymethacrylic acid, polymethacrylate, acrylonitrile, polyurethane resin, polyester resin, phenolic resin, epoxy resin, phenoxy resin, urea resin, melamine resin, cellulose resin, etc.
[0079] Based on the total solid content, the carbon black content in the coating solution for forming the negative electrode can be, for example, 0.5% by mass or more. From the viewpoint of further improving conductivity, it can also be 1% by mass or more, 2% by mass or more, or 5% by mass or more. Furthermore, based on the total solid content, the carbon black content in the coating solution for forming the negative electrode can be, for example, 30% by mass or less. From the viewpoint of avoiding a decrease in the content of the active material in the negative electrode due to an increase in carbon black content, it can also be 25% by mass or less, 20% by mass or less, or 10% by mass or less. That is, based on the total solid content, the carbon black content in the coating solution for forming the negative electrode can be, for example, 0.5–30% by mass, 0.5–25% by mass, 0.5–20% by mass, 0.5–10% by mass, 1–30% by mass, 1–25% by mass, 1–20% by mass, 1–10% by mass, 2–30% by mass, 2–25% by mass, 2–20% by mass, 2–10% by mass, 5–30% by mass, 5–25% by mass, 5–20% by mass, or 5–10% by mass.
[0080] Based on the total solid content, the content of the negative electrode active material in the coating solution for forming the negative electrode can be, for example, 90% by mass or more. From the viewpoint that increasing the content of the negative electrode active material can improve the energy density, it can also be 93% by mass or more, 94% by mass or more, or 95% by mass or more. Furthermore, based on the total solid content, the content of the negative electrode active material in the coating solution for forming the negative electrode can be, for example, 99% by mass or less. From the viewpoint that it is easier to improve the conductivity, adhesion, and dispersibility of the composite material layer, it can also be 98% by mass or less, 97% by mass or less, or 96% by mass or less. That is, based on the total amount of solids, the content of the negative electrode active material in the coating solution for forming the negative electrode can be, for example, 90-99% by mass, 90-98% by mass, 90-97% by mass, 90-96% by mass, 93-99% by mass, 93-98% by mass, 93-97% by mass, 93-96% by mass, 94-99% by mass, 94-98% by mass, 94-97% by mass, 94-96% by mass, 95-99% by mass, 95-98% by mass, 95-97% by mass, or 95-96% by mass.
[0081] Based on the total solids content, the binder content in the coating liquid for forming the negative electrode can be, for example, 0.5% by mass or more. From the viewpoint of further improving the adhesion of the composite layer, it can also be 1% by mass or more, 1.5% by mass or more, or 2% by mass or more. Furthermore, based on the total solids content, the binder content in the coating liquid for forming the negative electrode can be, for example, 10% by mass or less. From the viewpoint of easily obtaining lower electrode resistance, it can also be 5% by mass or less, 4% by mass or less, or 3% by mass or less. That is, based on the total solids content, the binder content in the coating liquid for forming the negative electrode can be, for example, 0.5–10% by mass, 0.5–5% by mass, 0.5–4% by mass, 0.5–3% by mass, 1–10% by mass, 1–5% by mass, 1–4% by mass, 1–3% by mass, 1.5–10% by mass, 1.5–5% by mass, 1.5–4% by mass, 1.5–3% by mass, 2–10% by mass, 2–5% by mass, 2–4% by mass, or 2–3% by mass.
[0082] When the coating solution for forming the negative electrode contains a dispersant, the content of the dispersant in the coating solution for forming the negative electrode, based on the total solid content, can be, for example, 0.1% by mass or more. From the viewpoint of further improving the viscosity and dispersibility of the coating solution for forming the negative electrode, it can also be 1% by mass or more, 1.5% by mass or more, or 2% by mass or more. Furthermore, based on the total solid content, the content of the dispersant in the coating solution for forming the negative electrode can be, for example, 4% by mass or less. From the viewpoint of easily obtaining lower electrode resistance, it can also be 3.5% by mass or less, 3% by mass or less, or 2.5% by mass or less. That is, based on the total amount of solids, the content of dispersant in the coating solution for forming the negative electrode can be, for example, 0-4% by mass, 0-3.5% by mass, 0-3% by mass, 0-2.5% by mass, 0.1-4% by mass, 0.1-3.5% by mass, 0.1-3% by mass, 0.1-2.5% by mass, 1-4% by mass, 1-3.5% by mass, 1-3% by mass, 1-2.5% by mass, 1.5-4% by mass, 1.5-3.5% by mass, 1.5-3% by mass, 1.5-2.5% by mass, 2-4% by mass, 2-3.5% by mass, 2-3% by mass, or 2-2.5% by mass.
[0083] The solid content concentration of the coating solution for forming the negative electrode can, for example, be 20% by mass or more, and from the viewpoint of coatingability and productivity, it can also be 25% by mass or more, 30% by mass or more, 35% by mass or more, or 40% by mass or more. Furthermore, the solid content concentration of the coating solution for forming the negative electrode can, for example, be 95% by mass or less, and from the viewpoint of coatingability, it can also be 90% by mass or less, 80% by mass or less, or 70% by mass or less. That is, the solid content concentration of the coating solution for forming the negative electrode can, for example, be 20–90% by mass, 20–80% by mass, 20–70% by mass, 25–90% by mass, 25–80% by mass, 25–70% by mass, 30–90% by mass, 30–80% by mass, 30–70% by mass, 35–90% by mass, 35–80% by mass, 35–70% by mass, 40–90% by mass, 40–80% by mass, or 40–70% by mass.
[0084] The coating solution for forming the negative electrode can be manufactured, for example, by the following method.
[0085] (Method for manufacturing coating liquid for negative electrode formation) The coating liquid for forming the negative electrode in this embodiment can be manufactured, for example, by a manufacturing method that includes a step of mixing the above-mentioned slurry, negative electrode active material and binder.
[0086] In the above process, an aqueous solvent may be further mixed. Furthermore, in the above process, a dispersant may be further mixed.
[0087] There are no particular limitations on the mixing method in the above process; any known mixing method can be appropriately selected.
[0088] A method for manufacturing a coating solution for forming a negative electrode may include, for example, a first mixing step of mixing the aforementioned slurry, an aqueous solvent, and a dispersant to obtain a first mixture; a second mixing step of mixing the first mixture with a negative electrode active material to obtain a second mixture; and a third mixing step of mixing the second mixture with a binder to obtain a coating solution for forming a negative electrode. According to this manufacturing method, it is easy to obtain an electrode with fewer aggregates and a uniform distribution of the negative electrode active material in the composite material layer.
[0089] By applying the negative electrode forming coating liquid of this embodiment onto the current collector and then drying it, a composite material layer can be formed on the current collector. The current collector and the composite material layer can be pressurized by rolling or the like. The negative electrode having the current collector and the composite material layer is suitable for use as a negative electrode in secondary batteries such as lithium-ion secondary batteries.
[0090] (negative electrode) The negative electrode of this embodiment includes a current collector and a composite material layer disposed on the current collector. The composite material layer may be a layer formed by a coating liquid for forming a negative electrode, containing carbon black, a negative electrode active material, and a binder. The composite material layer may further contain a dispersant.
[0091] There are no particular limitations on the current collector; for example, it can be appropriately selected from known current collectors used for the negative electrode of a secondary battery.
[0092] Examples of current collectors include metal foils (e.g., metals such as copper, gold, silver, copper, platinum, aluminum, iron, nickel, chromium, manganese, lead, tungsten, and titanium, as well as alloys with any one of these metals as the main component). Furthermore, current collectors with a carbon coating on the metal foil are also preferred.
[0093] Carbon black, negative electrode active material, binder and dispersant in composite material layers can be the same substances as those mentioned above.
[0094] The carbon black content in the composite material layer, based on the total amount of the composite material layer, can be, for example, 0.5% by mass or more. From the perspective of further improving conductivity, it can also be 1% by mass or more, 2% by mass or more, or 5% by mass or more. Furthermore, the carbon black content in the composite material layer, based on the total amount of the composite material layer, can be, for example, less than 30% by mass. From the perspective of avoiding a decrease in the content of negative electrode active material due to increased carbon black content, it can also be less than 25% by mass, less than 20% by mass, or less than 10% by mass. That is, the carbon black content in the composite material layer, based on the total amount of the composite material layer, can be, for example, 0.5–30% by mass, 0.5–25% by mass, 0.5–20% by mass, 0.5–10% by mass, 1–30% by mass, 1–25% by mass, 1–20% by mass, 1–10% by mass, 2–30% by mass, 2–25% by mass, 2–20% by mass, 2–10% by mass, 5–30% by mass, 5–25% by mass, 5–20% by mass, or 5–10% by mass.
[0095] The content of the negative electrode active material in the composite material layer, based on the total amount of the composite material layer, can be, for example, 90% by mass or more. From the viewpoint of expecting to improve energy density by increasing the content of negative electrode active material, it can also be 93% by mass or more, 94% by mass or more, or 95% by mass or more. Alternatively, the content of the negative electrode active material in the composite material layer, based on the total amount of the composite material layer, can be, for example, 99% by mass or less. From the viewpoint of more easily improving the conductivity, adhesion, and dispersibility of the composite material layer, it can also be 98% by mass or less, 97% by mass or less, or 96% by mass or less. That is, the content of the negative electrode active material in the composite material layer, based on the total amount of the composite material layer, can be, for example, 90–98% by mass, 90–97% by mass, 90–96% by mass, 93–98% by mass, 93–97% by mass, 93–96% by mass, 94–98% by mass, 94–97% by mass, 94–96% by mass, 95–98% by mass, 95–97% by mass, or 95–96% by mass.
[0096] The binder content in the composite layer, based on the total amount of the composite layer, can be, for example, 0.5% by mass or more. From the viewpoint of further improving the adhesion of the composite layer, it can also be 1% by mass or more, 1.5% by mass or more, or 2% by mass or more. Alternatively, the binder content in the composite layer, based on the total amount of the composite layer, can be, for example, 10% by mass or less. From the viewpoint of easily obtaining lower electrode resistance, it can also be 5% by mass or less, 4% by mass or less, or 3% by mass or less. That is, the binder content in the composite layer, based on the total amount of the composite layer, can be, for example, 0.5–10% by mass, 0.5–5% by mass, 0.5–4% by mass, 0.5–3% by mass, 1–10% by mass, 1–5% by mass, 1–4% by mass, 1–3% by mass, 1.5–10% by mass, 1.5–5% by mass, 1.5–4% by mass, 1.5–3% by mass, 2–10% by mass, 2–5% by mass, 2–4% by mass, and 2–3% by mass.
[0097] When the composite material layer contains a dispersant, the content of the dispersant in the composite material layer, based on the total amount of the composite material layer, can be, for example, 0.1% by mass or more. From the viewpoint of improving the dispersibility of each component in the composite material layer, it can also be 1% by mass or more, 1.5% by mass or more, or 2% by mass or more. Alternatively, the content of the dispersant in the composite material layer, based on the total amount of the composite material layer, can be, for example, 4% by mass or less. From the viewpoint of easily obtaining lower electrode resistance, it can also be 3.5% by mass or less, 3% by mass or less, or 2.5% by mass or less. That is, the content of dispersant in the composite material layer is based on the total amount of the composite material layer, and can be, for example, 0-4% by mass, 0-3.5% by mass, 0-3% by mass, 0-2.5% by mass, 0.1-4% by mass, 0.1-3.5% by mass, 0.1-3% by mass, 0.1-2.5% by mass, 1-4% by mass, 1-3.5% by mass, 1-3% by mass, 1-2.5% by mass, 1.5-4% by mass, 1.5-3.5% by mass, 1.5-3% by mass, 1.5-2.5% by mass, 2-4% by mass, 2-3.5% by mass, 2-3% by mass, or 2-2.5% by mass.
[0098] The thickness of the composite material layer can be, for example, 10 μm or more, or 30 μm or more, 50 μm or more, or 70 μm or more. In addition, the thickness of the composite material layer can be, for example, less than 400 μm, or less than 300 μm, less than 250 μm, less than 200 μm, less than 150 μm or less. That is, the thickness of the composite material layer can be, for example, 10–400 μm, 10–300 μm, 10–250 μm, 10–200 μm, 10–150 μm, 10–100 μm, 30–400 μm, 30–300 μm, 30–250 μm, 30–200 μm, 30–150 μm, 30–100 μm, 50–400 μm, 50–300 μm, 50–250 μm, 50–200 μm, 50–150 μm, 50–100 μm, 70–400 μm, 70–300 μm, 70–250 μm, 70–200 μm, 70–150 μm, or 70–100 μm.
[0099] The negative electrode of this embodiment can be manufactured, for example, by the following method.
[0100] (Method for manufacturing the negative electrode) The negative electrode of this embodiment can be manufactured, for example, by a method including a process of coating a negative electrode forming coating liquid onto a current collector to form a composite material layer on the current collector.
[0101] There are no particular limitations on the coating method of the coating solution for forming the negative electrode; an appropriate method can be selected from known coating methods.
[0102] A composite material layer is formed by removing the aqueous solvent from the coating solution used for forming the negative electrode coated on the current collector. There are no particular limitations on the method for removing the aqueous solvent; any known method may be appropriately selected.
[0103] Aqueous solvents can be removed, for example, by heating and drying. There are no particular limitations on the heating conditions; for example, they can be 60–250°C or 70–140°C.
[0104] The manufacturing method of the negative electrode may further include a process of pressing the current collector and the composite material layer.
[0105] There are no particular limitations on the pressing method; any known method can be appropriately selected. Examples of pressing methods include roller pressing and hot roller pressing. The pressing pressure is not particularly limited; for example, it can be 0.1–10 kN / cm or 0.3–6 kN / cm. The thickness of the composite material layer can be adjusted by pressing.
[0106] Since the negative electrode of this embodiment is formed using the above-described slurry, it has low electrode resistance and is suitable for use as a negative electrode for secondary batteries (e.g., lithium-ion secondary batteries).
[0107] The battery of this embodiment includes the aforementioned negative electrode. In the battery of this embodiment, the configuration other than the negative electrode can be the same as that of a known battery.
[0108] The battery in this embodiment may include, for example, a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrodes.
[0109] The battery of this embodiment has excellent battery characteristics due to the presence of a negative electrode with low electrode resistance.
[0110] The battery manufacturing method of this embodiment may include the step of manufacturing a negative electrode by the manufacturing method described above.
[0111] The preferred embodiments of this disclosure have been described above, but this disclosure is not limited to the above embodiments.
[0112] [Example] The present disclosure will be described in more detail below through embodiments, but the present disclosure is not limited to these embodiments.
[0113] (Example A-1: Preparation of slurry) Polyvinylpyrrolidone (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., model: K30, weight average molecular weight: 45,000) (hereinafter referred to as dispersant (1)) was mixed with water to prepare an aqueous solution of PVP (concentration: 2.385% by mass). Next, as carbon black, acetylene black with an average primary particle size of 19 nm (specific surface area: 301 m²) was prepared. 2 / g, DBP oil absorption: 340mL / 100g) (hereinafter referred to as CB(1)), 5.5g of CB(1) and 26.7g of PVP aqueous solution (60% of the PVP aqueous solution used) were added to a container and stirred at 2000rpm for 5 minutes using a Rentarō (THINKY Corporation, ARV-310). Next, 17.8g of PVP aqueous solution (40% of the PVP aqueous solution used) was added to the container and stirred further at 2000rpm for 5 minutes. Next, 100g of DBP oil absorption was added to the container. 0.5 mm zirconia beads were stirred in a rock-and-roll mill for 1.5 hours to prepare slurry (A-1) (solids concentration: 13.2% by mass). In slurry (A-1), the carbon black content, based on the total slurry volume, was 11% by mass, the solids content was 84% by mass, and the dispersant content was 19.3 parts by mass per 100 parts by mass of carbon black.
[0114] The particle size distribution and viscosity of the resulting slurry (A-1) were determined using the following method. The results are shown in Table 1.
[0115] <Determination of Particle Size Distribution> The volumetric particle size distribution of carbon black was determined by laser diffraction and scattering method using a particle size distribution measuring device (manufactured by MicrotracBEL, "Microtrac MT3300EX II" "Ultra-small Circulator USVR"), as follows.
[0116] (Measurement conditions) Measurement range: 0.02~2000μm Particle permeability: absorption Particle shape: Non-spherical Solvent: Water Loop output: 5 Sample input amount: Adjusted to the optimal concentration range displayed when the sample is input. Furthermore, the particle size distribution of carbon black measured here is not the particle size distribution of the primary particle size of carbon black, but rather the particle size distribution of the structure formed by the aggregation of primary carbon black particles.
[0117] <Viscosity Measurement> The viscosity of the slurry was determined using a viscoelasticity measuring device (manufactured by Anton Paar, “MCR302”) as follows.
[0118] (Measurement conditions) Measurement fixture: Conical plate (2°) Measurement temperature: 25℃ Shearing speed: 100s-1 →0.1s -1 Number of measurement points: 17 In addition, the viscosity listed in Table 1 is based on a shear rate of 10 s. -1 The value at time.
[0119] (Example A-2: Preparation of slurry) Except for using polyvinylpyrrolidone (Daiichi Kogyo Pharmaceutical Manufacturing Co., Ltd., model: K50) (hereinafter, dispersant (2)) with a weight-average molecular weight of 25,000 as polyvinylpyrrolidone, and changing the stirring time of the rocker mill to 5 hours, the slurry was prepared in the same manner as in Example A-1, and slurry (A-2) was obtained. For the obtained slurry (A-2), the particle size distribution and viscosity were measured in the same manner as in Example A-1. The results are shown in Table 1.
[0120] (Example A-3: Preparation of slurry) Except for using sodium carboxymethyl cellulose (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., 5A) (hereinafter, dispersant (3)) instead of polyvinylpyrrolidone, and changing the stirring time of the rocker mill to 3 hours, the slurry was prepared in the same manner as in Example A-1, and slurry (A-3) was obtained. For the obtained slurry (A-3), the particle size distribution and viscosity were measured in the same manner as in Example A-1. The results are shown in Table 1.
[0121] (Comparative Example X-1: Preparation of Slurry) In addition to using acetylene black with an average primary particle size of 23 nm (specific surface area: 133 m²), 2 / g, DBP oil absorption: 322mL / 100g) (hereinafter, CB(2)) was used as carbon black, and the stirring time of the rocker mill was changed to 0.5 hours. The slurry was prepared in the same manner as in Example A-1, and slurry (X-1) was obtained. For the obtained slurry (X-1), the particle size distribution and viscosity were measured in the same manner as in Example A-1. The results are shown in Table 1.
[0122] (Comparative Example X-2: Preparation of Slurry) In addition to using acetylene black with an average primary particle size of 48 nm (specific surface area: 39 nm), 2 / g, DBP oil absorption: 182mL / 100g) (hereinafter, CB(3)) was used as carbon black, and the stirring time of the rocker mill was changed to 0.5 hours. The slurry was prepared in the same manner as in Example A-1, and slurry (X-2) was obtained. For the obtained slurry (X-2), the particle size distribution and viscosity were measured in the same manner as in Example A-1. The results are shown in Table 1.
[0123] [Table 1]
[0124] (Example A-4: Preparation of slurry) Except for changing the amount of PVP aqueous solution to make the content of dispersant (2) in the slurry 15 parts by mass relative to 100 parts by mass of carbon black, the slurry was prepared in the same manner as in Example A-2, and slurry (A-4) (solids concentration: 12.65% by mass) was obtained. In addition, in slurry (A-1), the content of carbon black, based on the total amount of slurry, was 11% by mass, based on the total amount of solids, it was 86.96% by mass, and the content of dispersant was 15 parts by mass relative to 100 parts by mass of carbon black.
[0125] (Example A-5: Preparation of slurry) Except for changing the amount of PVP aqueous solution to make the content of dispersant (2) in the slurry 13 parts by mass relative to 100 parts by mass of carbon black, the slurry was prepared in the same manner as in Example A-2, and slurry (A-5) (solids concentration: 12.43% by mass) was obtained. In addition, in slurry (A-1), the content of carbon black, based on the total amount of slurry, was 11% by mass, based on the total amount of solids, it was 88.50% by mass, and the content of dispersant was 13 parts by mass relative to 100 parts by mass of carbon black.
[0126] (Example A-6: Preparation of slurry) Except for changing the amount of PVP aqueous solution to make the content of dispersant (2) in the slurry 11 parts by mass relative to 100 parts by mass of carbon black, the slurry was prepared in the same manner as in Example A-2, and slurry (A-6) (solids concentration: 12.21% by mass) was obtained. In addition, in slurry (A-1), the content of carbon black, based on the total amount of slurry, was 11% by mass, based on the total amount of solids, was 90.09% by mass, and the content of dispersant was 11 parts by mass relative to 100 parts by mass of carbon black.
[0127] The slurries obtained in Examples A-4 to A-6 have sufficient fluidity to drip when tilted at 90°, confirming that the carbon black is sufficiently dispersed.
[0128] (Example B-1: Fabrication of the negative electrode) 6.20 g of slurry (A-1) and 19.79 g of water were placed in a container and stirred using a Rentaro mixer (THINKY Corporation, ARV-310) at 2000 rpm for 5 minutes. Next, 55.07 g of sodium carboxymethyl cellulose aqueous solution (concentration: 1% by mass) was added and stirred using a Rentaro mixer at 200 rpm for 5 minutes. Next, 3.41 g of SiO2 (Shin-Etsu Chemical Co., Ltd., KSC-1262) was added and stirred using a Rentaro mixer at 200 rpm for 5 minutes. Finally, 62.10 g of graphite (Resonac Corporation, Model: MAGD) was added and stirred using a homogenizer (THINKY Corporation) at 200 rpm for 40 minutes. Next, 3.41g of styrene-butadiene rubber (manufactured by Zeon Corporation, Japan, BM-400B) as a binder was added, and the mixture was stirred at 500rpm for 2 minutes using Rentaro to obtain a coating solution for negative electrode formation (solid content concentration: 45% by mass).
[0129] The obtained negative electrode forming coating solution was coated onto copper foil and dried at 80°C for 1 hour. Then, it was rolled under conditions of a roll gap of 110 μm and 0.4 kN / cm to obtain a negative electrode (B-1) comprising copper foil and a composite material layer (82 μm). Furthermore, the coating of the negative electrode forming coating solution was carried out with a composite material layer weight per unit area of 12 mg / cm². 2 The density of the composite material layer is 1.4 g / cm³. 3 This is done in a certain way.
[0130] The obtained negative electrode (B-1) was evaluated using the following methods. The results are shown in Table 2.
[0131] <Electrode Resistance> The composite material resistance, interface resistance, and plate resistance of the negative electrode were determined using the following methods.
[0132] The resistance was measured using an electrode resistance meter (manufactured by Hioki Electric Co., Ltd., product name: RM2610), in the following operating modes: potential measurement + calculation, potential measurement: contact check threshold 1.07Ω, and voltage range within a range that would not overload the resistance value. The plate resistance value is the sum of the interface resistance between the negative electrode composite layer and the copper current collector, and the composite material resistance value of the negative electrode composite layer.
[0133] <Evaluation of Electrode Surface> Visually inspect the electrode surface and evaluate it according to A to D below.
[0134] A: The electrode surface has a uniform color and no unevenness caused by aggregates or scratches from scraping.
[0135] B: Patterns originating from the coating are visible on the electrode surface, but no unevenness caused by aggregates or scratches from electrode scraping are observed.
[0136] C: The electrode surface shows unevenness caused by aggregates, but no scratches from scraping are visible on the electrode.
[0137] D: The electrode surface shows unevenness caused by aggregates, as well as scratches from scraping the electrode.
[0138] (Example B-2: Fabrication of the negative electrode) Except that slurry (A-2) was used instead of slurry (A-1), the negative electrode (B-2) was prepared in the same manner as in Example B-1. The resulting negative electrode (B-2) was evaluated using the same method as in Example B-1. The results are shown in Table 2.
[0139] (Example B-3: Fabrication of the negative electrode) Except that slurry (A-3) was used instead of slurry (A-1), the negative electrode (B-3) was prepared in the same manner as in Example B-1. The resulting negative electrode (B-3) was evaluated using the same method as in Example B-1. The results are shown in Table 2.
[0140] (Comparative Example Y-1) 67.57 g of sodium carboxymethyl cellulose aqueous solution (concentration: 1% by mass) and 13.51 g of water were placed in a container and stirred using a Rentaro mixer (THINKY Corporation, ARV-310) at 2000 rpm for 5 minutes. Next, 0.68 g of CB (1) was added and stirred using a Rentaro mixer (THINKY Corporation, ARV-310) at 2000 rpm for 5 minutes. Next, 3.38 g of SiO (Shin-Etsu Chemical Co., Ltd., KSC-1262) was added and stirred using a Rentaro mixer at 200 rpm for 5 minutes. Next, 61.49 g of graphite (Resonac Corporation, model: MAGD) was added and stirred using a homogenizer (THINKY Corporation) at 2000 rpm for 40 minutes. Next, 3.38g of styrene-butadiene rubber (manufactured by Zeon Corporation, Japan, BM-400B) as a binder was added, and the mixture was stirred at 500 rpm for 2 minutes using Rentaro to obtain a coating solution for negative electrode formation (solid content concentration: 45% by mass).
[0141] Except for using the obtained coating liquid for forming the negative electrode, the negative electrode was prepared in the same manner as in Example B-1 to obtain the negative electrode (Y-1).
[0142] (Comparative Example Y-2) 54.53 g of sodium carboxymethyl cellulose aqueous solution (concentration: 1% by mass) and 13.51 g of water were placed in a container and stirred at 2000 rpm for 5 minutes using a stirring rod (THINKY Corporation, ARV-310). Next, 13.04 g of polyvinylpyrrolidone aqueous solution (concentration: 1% by mass) was added and stirred at 2000 rpm for 5 minutes using a stirring rod (THINKY Corporation, ARV-310). Next, 0.68 g of CB (1) was added and stirred at 2000 rpm for 5 minutes using a stirring rod (THINKY Corporation, ARV-310). Next, 3.38 g of SiO (Shin-Etsu Chemical Co., Ltd., KSC-1262) was added and stirred at 2000 rpm for 5 minutes using a stirring rod. Next, 61.49g of graphite (manufactured by Resonac, model: MAGD) was added and stirred using a homogenizer (manufactured by THINKY) at 2000 rpm for 40 minutes. Then, 3.38g of styrene-butadiene rubber (manufactured by Zeon Corporation, BM-400B) as a binder was added and stirred using a Rentarō mixer at 500 rpm for 2 minutes to obtain a coating solution for negative electrode formation (solid content concentration: 45% by mass).
[0143] Except for using the obtained coating liquid for forming the negative electrode, the negative electrode was prepared in the same manner as in Example B-1 to obtain the negative electrode (Y-2).
[0144] [Table 2]
[0145] (Comparative Example Y-3: Fabrication of the negative electrode) Except that slurry (X-1) was used instead of slurry (A-1), the negative electrode was prepared in the same manner as in Example B-1, and negative electrode (Y-3) was obtained. The obtained negative electrode (Y-3) was evaluated by the same method as in Example B-1. The results are shown in Table 3.
[0146] (Comparative Example Y-4: Fabrication of the negative electrode) Except that CB(2) was used instead of CB(1), the negative electrode was fabricated in the same manner as in Comparative Example Y-1, and a negative electrode (Y-4) was obtained. The obtained negative electrode (Y-4) was evaluated by the same method as in Example B-1. The results are shown in Table 3.
[0147] (Comparative Example Y-5: Fabrication of the negative electrode) Except that CB(2) was used instead of CB(1), the negative electrode was fabricated in the same manner as in Comparative Example Y-2, and a negative electrode (Y-5) was obtained. The obtained negative electrode (Y-5) was evaluated by the same method as in Example B-1. The results are shown in Table 3.
[0148] [Table 3]
[0149] (Comparative Example Y-6: Fabrication of the negative electrode) Except that slurry (X-2) was used instead of slurry (A-1), the negative electrode was prepared in the same manner as in Example B-1, and a negative electrode (Y-6) was obtained. The obtained negative electrode (Y-6) was evaluated using the same method as in Example B-1. The results are shown in Table 4.
[0150] (Comparative example Y-7: Fabrication of the negative electrode) Except that CB(3) was used instead of CB(1), the negative electrode was fabricated in the same manner as in Comparative Example Y-1, and a negative electrode (Y-7) was obtained. The obtained negative electrode (Y-7) was evaluated by the same method as in Example B-1. The results are shown in Table 4.
[0151] (Comparative example Y-8: Fabrication of the negative electrode) Except that CB(3) was used instead of CB(1), the negative electrode was fabricated in the same manner as in Comparative Example Y-2, and a negative electrode (Y-8) was obtained. The obtained negative electrode (Y-8) was evaluated by the same method as in Example B-1. The results are shown in Table 4.
[0152] [Table 4]
Claims
1. A carbon black slurry for negative electrode formation, comprising carbon black with an average primary particle size of less than 22 nm and an aqueous solvent. Based on the total solids content, the carbon black content is 50% by mass or more. In the volume-based particle size distribution determined by laser diffraction and scattering, the median particle size D50 of the carbon black is greater than 0.1 μm and less than 1 μm.
2. The carbon black slurry for negative electrode formation according to claim 1, further comprising a dispersant.
3. The carbon black slurry for negative electrode formation according to claim 2, wherein the content of the dispersant is 10 parts by mass or more and 25 parts by mass or less relative to 100 parts by mass of the carbon black.
4. The carbon black slurry for negative electrode formation according to claim 2, wherein the dispersant is selected from the group consisting of polyvinylpyrrolidone and sodium carboxymethyl cellulose.
5. The carbon black slurry for forming a negative electrode according to claim 1, wherein the specific surface area of the carbon black is 150 m². 2 / g or more and 400m 2 / g or less.
6. The carbon black slurry for negative electrode formation according to claim 1, wherein the aqueous solvent is water, and the content of the organic solvent is less than 1% by mass.
7. A method for manufacturing a coating liquid for negative electrode formation, comprising a step of mixing a carbon black slurry for negative electrode formation, a negative electrode active material, and a binder as described in any one of claims 1 to 6.
8. A method for manufacturing a negative electrode, comprising a step of coating a negative electrode forming coating liquid manufactured by the manufacturing method of claim 7 onto a current collector to obtain a negative electrode having the current collector and a composite material layer disposed on the current collector.
9. A method for manufacturing a battery, comprising a step of coating a negative electrode forming coating liquid manufactured by the manufacturing method of claim 7 onto a current collector to obtain a negative electrode having the current collector and a composite material layer disposed on the current collector.
Citation Information
Patent Citations
Electrode for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and battery pack
JP2016181414A
